Marcel Proust ve Ahmet Hamdi Tanpınar'ın Kahramanlarının Resme İlgileri ve Portre Betimlemeleri - Günday, Rıfat (Kitabevi, 2003)
In the works of Proust and Tanpınar, the traces of the art of drawing and painting are retlected in the presentation of every element. So me of their characters are paintists and some are interested in art and have the culture of it. Many artists contributed Proust and Tanpınar to form aesthetics in the description of their portraits. The writers in question, as in the description of landscapes, use multidimension to represent portraits because of the different perspectives and the reflection of visionary dimension. As a conclusion of these techniques, Proust and Tanpınar introduced not only one - known portrait but also many sided ones of a single character, out of their impressions to the readers.
Marcel Proust and Ahmet Harndi Tanpınar's Characters' lnterest in Drowing and Descriptions of Portrait
Keywords: Portrait; Differences of Perspective; Visionary Dimension; Prooust; Tanpınar